Pelatihan Pembuatan Media Audiovisual dalam Meningkatkan Kemampuan Kreatif Digital Remaja - Riza Hayati Ifroh; Lies Permana (Jurnal Pengabdian Pada Masyarakat, 2021)
AUDIOVISUAL MEDIA CREATION TRAINING IN IMPROVING YOUTH'S DIGITAL CREATIVE CAPABILITIES. To face the challenges of the future industry, youth as millennials, they need a soft skill training to develop their skills in creating audiovisual media that is growing up in the era of industrial revolution 4.0. This activity is using The Training Cycle approach. The stage is to identify training needs, set training and planning objectives, the implementation of the training ends with an evaluation. The method activities based on the training cycle model and implemented in combination, i.e., lecture methods, video playback, questions and answers and also field practices. On the output evaluation is to identify the participant’s cognitive enhancement based on the assessment pre-test and post-test form filling by the participants, and to assess the participant’s responses related to training satisfaction (facilities, the committee, and the speaker). The results of the training evaluation, known that is an increase in the number of correct answers in the basic audiovisual concept question items, advantages and types of audiovisual media and about the process of creating audiovisual media and short movie concepts. In addition, based on the results of activity evaluation, the participants considered that they were satisfied following each series of training.